Penguatan Resiliensi dan Daya Saing Usaha Kuliner Pesisir melalui Digitalisasi Pemasaran di Desa Kedonganan, Kabupaten Badung, Bali - Anak Agung Ayu Arun Suwi Arianty; Ni Luh Gede Sari Dewi Astuti; Luh Eka Susanti; Febrina Endjitrie Renanda; I Kadek Agus Andika Pratama (Civiliza Publishing, 2026)
Kedonganan Village, Badung Regency, Bali, is a coastal area widely recognized as a seafood culinary center and an important component of Bali’s tourism system. However, post-pandemic dynamics have revealed that coastal culinary businesses continue to face several challenges, including low digital literacy, limited technology based marketing capabilities, and increasing destination competition. This community service program aimed to enhance the digital capacity of local culinary entrepreneurs through the optimization of Google Business Profile and the use of social media as an area-based digital marketing strategy. The program was implemented through workshops, training sessions, hands-on mentoring, and evaluation using pre-tests and post-tests involving 40 participants. The training materials covered the creation and management of digital business profiles, social media content strategies, product photography techniques, and business branding enhancement. The results demonstrated a significant improvement in participants’ knowledge and skills. In the Google Business Profile training, the average score increased from 54.8 to 84.6. Meanwhile, in the social media training, the average score rose from 58.4 to 82.2. Beyond knowledge improvement, participants also showed better capabilities in managing their digital business identity, increasing business visibility, and building stronger customer engagement through digital platforms. These findings indicate that the integration of Google Business Profile and social media represents an effective strategy for strengthening the competitiveness and resilience of coastal culinary businesses. The program also highlights the importance of community based approaches and institutional collaboration in accelerating the digital transformation of MSMEs within tourism destinations.